The Path and Strategy of High-Quality Development of Underdevelopment Area Elementary Education: A Case Study Based on “Double Hundred Projects” in Guizhou, China - Hu, Yuxi (Journal of China-ASEAN Studies, 2023)
Improving the quality of basic education in underdeveloped regions is a global issue, and the purpose of this study is to explore existing experiences and provide solutions that can be used as references. China’s economically impoverished province of Guizhou Province has implemented a five-year "Double Hundred Project" project in ethnic minority areas, and the government has provided financial funds for the construction of the project and purchased professional services through market mechanisms. This educational program provides an empirical basis for this research. Through the case analysis of school surveys, interviews, classroom observations and other methods, this study conducted a policy evaluation study on the project, and found that the well-designed "Double Hundred Project" is like "drip irrigation", which concentrates resource advantages and accurately supports the project objects, so that they can change the project objects in a short time; The institutional design of the third-party professional services supporting the project has helped the project object to realize the sinking of high-quality professional resources, and maximized the educational benefits of limited financial funds. It has changed the routine practice of "emphasizing quantity but not guaranteeing quality" and the disconnection between teacher training and teaching site, and innovated the teacher training model. It provides useful reference and enlightenment for supporting the design of high-quality basic education projects in underdeveloped areas